Methodological proposal for the analysis of environmental vulnerability to a possible spill of polyducts and oil pipelines - Blanco Castañeda, Oscar Mauricio; Camargo Millán, Gloria Lucia (Revista Mexicana de Ciencias Agrícolas, 2020)
The hydrocarbon industry in Colombia is one of the most dynamic, compared to other mining production fronts. Hydrocarbons have become fundamental elements for the development of society, in the economic, political, environmental and social fields. However, its exploitation, together with the topographic and climatological characteristics of Colombia, have become a threat to the environment, since the probability of a spill is high, which directly or indirectly has toxic effects on fauna, flora, bodies of water and the general population. These alterations cause interference in the reproduction, growth and behavior of animals. They affect root systems causing leaf fall and tree death. Additionally, it causes economic losses and migration of the affected population, due to the difficulty of quickly eliminating the pollutant, which causes short, medium and long-term impacts.
Keywords: hydrocarbons; mining; pollutant